Vegetation analysis and ethnobotanical study of rubber agroforests in South Sumatra, Indonesia - SYAIFUL EDDY; SYAMSUL RIZAL; TRIMIN KARTIKA; KESI JUWITA SARI (Society for Indonesian Biodiversity, 2023)
Abstract. Eddy S, Rizal S, Kartika T, Sari KJ. 2023. Vegetation analysis and ethnobotanical study of rubber agroforests in South Sumatra, Indonesia 24: 2276-2283. Rubber agroforests (RA) play essential roles in conserving plant biodiversity and delivering ecosystem services while providing socio-economic benefits to local communities. This study aims to examine the composition and structure of vegetation and to explore the ethnobotanical uses of plants in rubber agroforests located in Southern Tempirai Village, North Penukal Sub-district, Penukal Abab Lematang Ilir (PALI) District, South Sumatra, Indonesia. Vegetation data were collected using the purposive sampling method in three different rubber agroforests by establishing transect lines and observation plots according to the plant life form (seedling, sapling, and tree) at each sampling point. Ethnobotanical data were collected through interviews with plant-using communities through a purposive sampling method. The results showed that there were 17 plant species belonging to 13 families documented in the studied area. The most dominant species at seedling stage (including understorey) was senduduk (Melastoma malabathricum) with an IVI (Important Value Index) of 38.79, while the most dominant species at sapling and tree layers was rubber (Hevea brasiliensis) with IVI of 185.48 and 300.00, respectively. In the rubber agroforests studied, the species diversity was classified as very low with a diversity index (H') value of 0.85. There are various ethnobotanical uses plants found in the rubber agroforest with the most common use by the community was for traditional medicines (Mimosa pudica, Melastoma malabathricum, Gleichenia linearis, Ageratum conyzoides, Piper betle, Stenochlaena palustris, Coffea sp., Salacca zalacca, Syzygium polyanthum, Sauropus androgynus, Imperata cylindrica, Areca catechu). Other uses were for food ingredients (Calamus sp., Coffea sp., Bambusa sp, Salacca zalacca, Syzygium polyanthum, Sauropus androgynus), building materials (Hevea brasiliensis, Areca catechu), and household furniture (Calamus sp., Bambusa sp.). This study enriches the understanding regarding the importance of rubber agroforest in conserving germplasm diversity and maintaining the ethnobotanical knowledge of local communities.